Nilai-Nilai Moderasi Beragama Dalam Materi PAI Dan Budi Pekerti Fase E Kurikulum Merdeka - Salamudin, Ceceng; Nuralamin, Firman (STAI Al-Musaddadiyah Garut, 2024)
This research examines the values of religious moderation in PAI material and character in phase E of the independent curriculum which emphasizes increasing projects to strengthen students' profiles of Pancasila and religious moderation as well as instilling the values of religious moderation which can be done in various ways, one of which is through teaching materials. This research aims to describe the scope of PAI material and morals in phase E of the independent curriculum, the values of religious moderation in PAI material and morals in phase E of the independent curriculum, and the relevance of religious moderation values to the independent curriculum. This research uses library research methods, namely by reading and analyzing library sources. The research results are presented in the form of a qualitative description, namely by describing the data obtained in depth and comprehensively from data sources and references. Content analysis technique is used to analyze data obtained from data sources. This research concludes. First, the scope of the Islamic Education and Character Education textbook in phase E of the independent curriculum contains ten chapters. Each chapter in this textbook contains 11 rubrics (sub-material or parts of the text that are printed to make them stand out). Second, this textbook contains the values of religious moderation. The values of religious moderation in question are, At-Tawassuth (middle), I`tidal (perpendicular), Tasamuh (tolerance), Ash-Shura (deliberation), Al-Ishlah (repair), Al-Qudwah (Exemplary ), Al-Muwathanah (love of the homeland), Al-La`unf (non-violence), and I`tiraf Al-`Urf (culturally friendly). The presentation of moderation values in the textbook is through material, explicit or implied messages through material and illustrative images. Third, the values of religious moderation are important values to instill in students. These values can help students to understand, appreciate and practice their religious teachings correctly in accordance with the concept of religious moderation. The independent curriculum is a curriculum that is relevant to the values of religious moderation, which focuses on the project of strengthening the profile of Pancasila students, one of whose dimensions is faith, devotion to God Almighty and having noble morals. The values of religious moderation can be taught to students through differentiated learning that is adapted with the needs and abilities of each student. Keywords: Religious Moderation Values, Islamic Education and Ethics Materials, Independent Curriculum.